PROSEDUR PENANGANAN BARANG BAWAAN TAMU GROUP PADA SAAT CHECK IN OLEH BELLBOY DI HOTEL CONRAD BALI RESORT AND SPA NUSA DUA - Kadek Ananta Kesuma; I Made Suwitra Wirya; Ni Luh Putu Sri Widhiastuty (Universitas Triatma Mulya, 2021)
This research aims to describe the procedure of handling group check in guests wnd the barriers Each staff would like to give best service to guests including bell boy staff in Conrad Bali Resort and Spa is one of the hotels in Nusa Dua, Bali t. Satisfying service to guests shows employee professionalism in service to guests. In serving guests the check in bell boy group has an important role in achieving first-time guest satisfaction. As a Bell Boy staff handling items is very important because guest goods contain very valuable things and must be sent according to the room number that the guest has received and in accordance with standard operational procedures. Not only delivering goods, a bell boy can promote hotels and sell facilities owned. The author conducted research at Conrad Bali Resort and Spa with qualitative descriptive analysis. The author finds that the oprational procedure standard in handling the guests' luggage is checked in, a bell boy is very influential in working as a reference in implementing the bell boy according to his duties and responsibilities. A bell boy works based on operational standard procedures but in its implementation without following step by step the rules exist on the grounds that the situation and conditions when we serve goods and guests get constraints such as items that very much make goods late and guests assume they have lost their goods The bell boy must identify the item and lack professionalism in handling goods reduces the risk of errors that occur. In accordance with the management's research or supervisor will provide training to a bell boy and always monitor the service of a bell boy, with the aim of the bell boy staff knowing the importance of operational standard procedures to maintain the quality of service at Conrad Bali Resort and Spa.